2021
DOI: 10.1117/1.jbo.26.4.043010
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz scanning of the rabbit cornea with experimental UVB-induced damage: in vivo assessment of hydration and its verification

Abstract: . Significance: Water content plays a vital role in the normally functioning visual system; even a minor disruption in the water balance may be harmful. Today, no direct method exists for corneal hydration assessment, while it could be instrumental in early diagnosis and control of a variety of eye diseases. The use of terahertz (THz) radiation, which is highly sensitive to water content, appears to be very promising. Aim: To find out how THz scanning parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The relationship between corneal pathology changes due to B-band ultraviolet (UVB) radiation and parameters derived from the THz reflection coefficient of rabbit cornea has been investigated. 53 In an in vivo test, the amount of water in the cornea was measured simultaneously with the RC reflection coefficient. In general, corneal hydration can be determined with the help of the THz reflection coefficient, which can be effective in eye pathology.…”
Section: Corneal Water In Visual Diseasesmentioning
confidence: 99%
“…The relationship between corneal pathology changes due to B-band ultraviolet (UVB) radiation and parameters derived from the THz reflection coefficient of rabbit cornea has been investigated. 53 In an in vivo test, the amount of water in the cornea was measured simultaneously with the RC reflection coefficient. In general, corneal hydration can be determined with the help of the THz reflection coefficient, which can be effective in eye pathology.…”
Section: Corneal Water In Visual Diseasesmentioning
confidence: 99%
“…For instance, Iomdina et al, reported on the study of transmittance and reflectance of the cornea and sclera in the range of 0.13 to 0.32 THz followed by exposure to a backward-wave oscillator (BWO) with an effective bandwidth frequency of 10 MHz [ 13 ]. In another study, they explored the THz scanning of hydration of corneal tissue followed by damage caused by B-band ultraviolet (UVB) exposure at 50 Hz [ 14 ], while some studies have investigated THz sensing of ocular tissues, no studies have previously reported on the use of synchrotron continuous THz radiation source for both exposing and evaluating biological changes in corneal tissues or other ocular tissues. Furthermore, the mentioned studies do not contain the frequencies under consideration for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…1 ), has been observed during the past few decades, 1 5 driven by rapid progress in THz technology. 6 , 7 Numerous research papers demonstrate the potential of THz technology in label-free early noninvasive, least-invasive, and intraoperative diagnosis of malignant and benign neoplasms with different nosologies and localizations, 3 , 4 , 8 18 sensing of glycated tissues and blood in the context of diabetes diagnosis, 1 , 19 21 determining the degree of traumatic injuries, 22 25 hydration levels, 26 29 and viability 30 of tissues. Along with the diagnostic applications, THz technology holds strong potential in therapeutics, 31 , 32 for example, in nonthermal regulation in expression of genes associated with cancer and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%